Technological Monopoly of English for Informatics (Technopoly Etics) to Improve Student Motivation in Learning English - Wicaksono, Bayu Hendro; Widodo, Estu; Sumarsono, Puji; Dharmala, Bayu; Robania, Innayatul (LPPM Universitas Bumigora Mataram, 2020)
Student motivation comes out as a pivotal element in learning English. The presence of an interesting and joyful class environment is indispensably necessary to keep the student motivation up in following the whole learning activities. One out of the ways to increase student motivation in learning English is by employing supportive instructional media. Here, the researchers applied Technopoly Etics, an accustomed board combined from monopoly and technology (QR code). The data were gathered through observation (teaching activities) and interview. The findings show that student motivation and participation in following the class gradually rose once being taught with the aforementioned media.